Establecimiento agroproductivo ecologico vs. agricultura convencional: Partido de Tandil, Provincia de Buenos Aires / Organic agroproductive facility vs. Conventional agriculture: Tandil county, Buenos Aires province - Patricia Vazquez; Milagros Vignolles (Sociedade & Natureza)
In Argentina, in recent decades, a process known as “agriculturization” has been generated with various environmental impacts. This has led to introducing more sustainable farming models. This paper aims to analyze the sustainability of a rural facility dedicated to organic farming in comparison with conventional agricultural systems located in Tandil, Buenos Aires Province.